Mathematical approaches for understanding harmful algal blooms in West Coast of Sabah - Fatin Nadiah Mohamed Yussof; Normah Maan (Penerbit Universiti Kebangsaan Malaysia, 2025)
Massive algal growth at a certain region and period has alarmed the nation for the past years. The algal bloom is said to be harmful due to its damaging effect on marine creatures, economic sectors such as aquaculture and tourism, and human health. Mathematical modelling of Harmful Algal Blooms (HABs) is developed to describe the HAB’s dynamic on theWest Coast of Sabah for its annual bloom. There are four variables used in the developed model which are nutrient concentration, Toxic-Producing Phytoplankton (TPP) population, Non-Toxic Phytoplankton (NTP) population, and Zooplankton (Z) population. There exist interaction between all the variables where the nutrient is the food source for the TPP and NTP population. TPP population released toxin while the NTP population does not secrete out toxin chemicals, but it gives competition to the TPP population in terms of food. Zooplankton population act as a predator toward TPP and NTP population. The model is modified from Lotka-Volterra preypredator model and the stability of the model is also examined. TPP species released toxin to the environment and the effects of toxin on the stability of steady states is investigated. The results show that the system is unstable when TPP species released toxin to the environment and lead to the occurrence of HAB. Zooplankton population are harmed if they consumed TPP species if the toxin content is at peak. Besides, the results also shows that interspecies competition exist between NTP species and TPP species in order to get food. Therefore, this research gives information on how HAB could occur with the biological factors involved.